2017
DOI: 10.1007/s12687-017-0316-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and inclusion in genomic research: why the uneven progress?

Abstract: Conducting genomic research in diverse populations has led to numerous advances in our understanding of human history, biology, and health disparities, in addition to discoveries of vital clinical significance. Conducting genomic research in diverse populations is also important in ensuring that the genomic revolution does not exacerbate health disparities by facilitating discoveries that will disproportionately benefit well-represented populations. Despite the general agreement on the need for genomic researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
185
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(188 citation statements)
references
References 95 publications
0
185
2
1
Order By: Relevance
“…A study exploring the views of people from UK Black African and Black Caribbean communities showed a lack of organizational commitment, economic support, policies, practice, strategic vision, and leadership in engaging these participants in the 100,000 genomes project (Skyers, 2018). Literature focusing on ethnic disparities in genomic research has shown the need for a global approach, strategic vision, funding, development of skilled workforce, and community engagement programs promoting equitable access to genomics (Bentley et al, 2017; Mathew et al, 2017), but little progress has been made yet.…”
Section: Introductionmentioning
confidence: 99%
“…A study exploring the views of people from UK Black African and Black Caribbean communities showed a lack of organizational commitment, economic support, policies, practice, strategic vision, and leadership in engaging these participants in the 100,000 genomes project (Skyers, 2018). Literature focusing on ethnic disparities in genomic research has shown the need for a global approach, strategic vision, funding, development of skilled workforce, and community engagement programs promoting equitable access to genomics (Bentley et al, 2017; Mathew et al, 2017), but little progress has been made yet.…”
Section: Introductionmentioning
confidence: 99%
“…these mechanisms with cutting-edge treatments, and develop strategies to tailor each therapy to an individual's unique genetic profile and lifestyle (Bentley, Callier, & Rotimi, 2017). In 2007, the Genomics and Personalized Medicine Act was passed by the United States Congress, and research efforts ramped up drastically in January 2015 with the implementation of the Precision Medicine Initiative by President Barack Obama (Adams & Petersen, 2016;Barlas, 2015).…”
mentioning
confidence: 99%
“…One challenge is that it cannot be assumed that precision medicine will be “actionable” in real‐world settings or that all patients stand to benefit equally (Bayer and Galea ). The cultural and structural context of underserved racial/ethnic groups and economically challenged populations can impact how members of these groups think about a nd act on their health (Egede ; Williams et al ; Williams et al ); therefore, it is important to understand how diverse patients may regard aspects of precision medicine in order to optimize implementation (Bentley et al ). Additionally, individuals with lower health literacy may have less familiarity to concepts in precision medicine and may be unaware of gaps in their existing knowledge, and how to best apply new information to workable solutions (Paasche‐Orlow and Wolf ; Sorensen et al ).…”
Section: Introductionmentioning
confidence: 99%